Production and Optimization of Exopolysaccharides (EPS) Using Low-cost Bagasse as Substrate by Lysinibacillus macroides - Andharia, Kartik; Shilpkar, Prateek; Kundu, Susanta (Asian Journal of Biological and Life Sciences)
Exopolysaccharides are the secondary metabolites produced by many microorganisms and play a role as biopolymers extensively to protect living cells in various ways. In the present study, the carbon source was substituted by various cheaper agricultural wastes, investigated for EPS production, and found bagasse more suitable substrate than others. Bagasse at a concentration of 5% gave the highest EPS production of 13.13 ± 0.44 g L-1. The effect of various parameters like incubation period, agitation speed, inoculum size, pH, and the temperature was also studied and found to have the highest EPS production after an incubation time of 120 hr (15.10 g L-1), agitation speed of 100 rpm (12.47 g L-1), 10% inoculum size (13.43 g L-1), pH 7 (11.47 g L-1) and incubation temperature 30°C (13.17 g L-1). Thus, the present study confirmed that agricultural wastes could be a cheaper substitute for synthetic and expensive carbon substrates, which economically opens a new door toward EPS production.
Keywords: Agricultural wastes; Bagasse; Exopolysaccharides; Optimization.